1994
DOI: 10.1084/jem.180.3.783
|View full text |Cite
|
Sign up to set email alerts
|

Tissue expression of inducible nitric oxide synthase is closely associated with resistance to Leishmania major.

Abstract: Sunlmar~Previous studies with inhibitors of inducible nitric oxide synthase (iNOS) suggested that highoutput production of nitric oxide (NO) is an important antimicrobial effector pathway in vitro and in vivo. Here, we investigated the tissue expression of iNOS in mice after infection with Leishmania major. Immunohistochemical staining with an iNOS-specific antiserum revealed that in the cutaneous lesion and draining lymph nodes (LN) of clinically resistant mice (C57BL/6), iNOS protein is found earlier during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
198
1
4

Year Published

1997
1997
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 280 publications
(225 citation statements)
references
References 65 publications
21
198
1
4
Order By: Relevance
“…We show that the lymph nodes and spleens of mice infected with any of the tested parasite strains are devoid of detectable iNOS mRNA during the first week. This is in agreement with experiments by Stenger et al in which infection of Balb/c with L. major did not result in substantial iNOS transcription until week 5 [28].…”
Section: Discussionsupporting
confidence: 93%
“…We show that the lymph nodes and spleens of mice infected with any of the tested parasite strains are devoid of detectable iNOS mRNA during the first week. This is in agreement with experiments by Stenger et al in which infection of Balb/c with L. major did not result in substantial iNOS transcription until week 5 [28].…”
Section: Discussionsupporting
confidence: 93%
“…2 shows that this is not the case. It can be seen, in agreement with some recent reports (17)(18)(19)(20)(21), that PEC from two Th1-like strains (C57BL/6 and B10D2) are more easily activated by IFN-␥ to produce NO than macrophages from the two Th2-like strains (BALB/c, DBA/2). The concentration of citrulline, the other product of the iNOS pathway, parallels that of NO, as would be expected.…”
Section: Differential Arginine Metabolism By Th1 and Th2 Macrophagessupporting
confidence: 81%
“…Whereas the aforementioned results clearly indicate that T lymphocytes from different strains of mice have a tendency to produce cytokines that activate or inhibit macrophages, other reports have shown that macrophages from the Th1 strains are more easily activated than those from Th2 strains (17)(18)(19)(20)(21). Thus, the ability to generate a Th1-or Th2-type response does not wholly depend on T lymphocytes.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…A Th1 immune response leads to the induction of iNOS, which results in production of nitric oxide (NO), which is essential for killing the parasite. [14][15][16] In contrast, Th2 cytokines stimulate arginase production, which reduces killing capacity. [17][18][19] Therefore, proper activation and maturation of antigen-presenting cells (APCs) resulting in Th1 immunity is fundamental to parasite control.…”
Section: Discussionmentioning
confidence: 99%